The Substance of Indonesian Women Directors in Creating Value - Saarce Elsye Hatane; Sylvia Natasha Sinaga; Hendri Kwistianus; Tristan Nguyen (Jurnal Akuntansi dan Keuangan, 2025)
This paper aims to provide insight into the impact of the existence of female directors in the board of directors on firm value by taking into consideration the educational level and tenure of women directors in the governance of Indonesia’s companies. The hypotheses are tested on 177 Indonesian listed companies in the IDX between 2015-2020, manufacturing and retail industries, using the weighted least squares regressions. The evidence conveys that the educational level rather than the simple presence of women directors can increase firm value. Additionally, results reveal that the tenure of women is negatively related to firm value, as it might impair the board's independence. This study explores the potential of women on board through their educational level and tenure in the firms. Future studies may expand to include factors such as family background, reputation, and other personal or professional elements that can enhance women's performance in companies. Few studies have addressed the impact of women across different industries, especially in developing economies. This research contributes by examining the demographic variables of women board members that are still poorly apprehended (i.e. their educational level and tenure) in such a setting.